Financial Literacy in the Elementary Classroom: Integrate not Recreate - Gold, Lindsay A (Ohio Journal of School Mathematics, 2018)
Recently, Ohio has adopted a set of Financial Literacy standards for Grades K–12. While these guidelines might be familiar to the older grades, this is a new requirement for the elementary levels. What is important for primary educators to understand is that the new standards are not to be seen as an isolated set, but rather a way of including financial concepts and skills purposefully into an already established curriculum. This article discusses the notion of incorporation along with the meaning of financial literacy in the elementary classroom and why it is important for our young students.